High-Pressure Structural Behavior and Equation of State of Kagome Staircase Compound, Ni3V2O8 - Daniel Diaz-Anichtchenko; Robin Turnbull; Enrico Bandiello; Simone Anzellini; Daniel Errandonea (Crystals, 2020)
We report on high-pressure synchrotron X-ray diffraction measurements on Ni3V2O8 at room-temperature up to 23 GPa. According to this study, the ambient-pressure orthorhombic structure remains stable up to the highest pressure reached in the experiments. We have also obtained the pressure dependence of the unit-cell parameters, which reveals an anisotropic compression behavior. In addition, a room-temperature pressure–volume third-order Birch–Murnaghan equation of state has been obtained with parameters: V0 = 555.7(2) Å3, K0 = 139(3) GPa, and K0′ = 4.4(3). According to this result, Ni3V2O8 is the least compressible kagome-type vanadate. The changes of the crystal structure under compression have been related to the presence of a chain of edge-sharing NiO6 octahedral units forming kagome staircases interconnected by VO4 rigid tetrahedral units. The reported results are discussed in comparison with high-pressure X-ray diffraction results from isostructural Zn3V2O8 and density-functional theory calculations on several isostructural vanadates.